Microtubules provide force to promote membrane uncoating in vacuolar escape for a cyto-invasive bacterial pathogen - Yuen-Yan Chang; Camila Valenzuela; Arthur Lensen; Noelia Lopez-Montero; Saima Sidik; John Salogiannis; Jost Enninga; John Rohde (Nature Communications, 2024)
Abstract Intracellular bacterial pathogens gain entry to mammalian cells inside a vacuole derived from the host membrane. Some of them escape the bacteria-containing vacuole (BCV) and colonize the cytosol. Bacteria replicating within BCVs coopt the microtubule network to position it within infected cells, whereas the role of microtubules for cyto-invasive pathogens remains obscure. Here, we show that the microtubule motor cytoplasmic dynein-1 and specific activating adaptors are hijacked by the enterobacterium Shigella flexneri. These host proteins were found on infection-associated macropinosomes (IAMs) formed during Shigella internalization. We identified Rab8 and Rab13 as mediators of dynein recruitment and discovered that the Shigella effector protein IpaH7.8 promotes Rab13 retention on moving BCV membrane remnants, thereby facilitating membrane uncoating of the Shigella-containing vacuole. Moreover, the efficient unpeeling of BCV remnants contributes to a successful intercellular spread. Taken together, our work demonstrates how a bacterial pathogen subverts the intracellular transport machinery to secure a cytosolic niche.